Trait‐based approach confirms the importance of propagule limitation and assembly rules in old‐field restoration - Halassy, Melinda; Botta‐Dukát, Zoltán; Csecserits, Anikó; Szitár, Katalin; Török, Katalin (Restoration ecology, 2019)
Community assembly theory is suggested as a guiding principle for ecological restoration to help understand the mechanisms that structure biological communities and identify where restoration interventions are needed. We studied three hypotheses related to propagule limitation, stress‐dominance, and limiting similarity concepts in community assembly in a restoration field experiment with a trait‐based null model approach. The experiment aimed to assist the recovery of sand grassland on former arable land in the Kiskunság, Pannonian biogeographic region, Europe. Treatments included initial seeding of five grassland species, carbon amendment, low‐intensity mowing, and combinations in 1 m by 1 m plots in three old fields from 2003 to 2008. The distribution of 10 individual plant traits was compared to the null model and the effect of time and treatments were tested with linear mixed effect models. Initial seeding had the most visible impact on species and trait composition confirming propagule limitation in grassland recovery. Reducing nutrient availability through carbon amendment strengthened trait convergence for length of flowering as expected based on the stress‐dominance hypothesis. Mowing changed trait divergence to convergence for plant height with a strengthening impact with time, supporting our hypothesis of increasing dominance of limiting similarity with time. Our results support the idea that community assembly is simultaneously influenced by propagule limitation and multiple trait‐based processes that act through different traits. The limited impact of manipulating environmental filtering and limiting similarity compared to seeding, however, supports the view that only targeting the dispersal and environmental filters in parallel would improve restoration outcome.